Life‐history syndromes: Integrating dispersal through space and time. (1st April 2014) - Buoro, Mathieu; Carlson, Stephanie M.; Clobert, Jean
Abstract Recent research has highlighted interdependencies between dispersal and other life‐history traits, i.e. dispersal syndromes, thereby revealing constraints on the evolution of dispersal and opportunities for improved ability to predict dispersal by considering suites of dispersal‐related traits. This review adds to the growing list of life‐history traits linked to spatial dispersal by emphasising the interdependence between dispersal through space and time, i.e. life‐history diversity that distributes individuals into separate reproductive events. We reviewed the literature that has simultaneously investigated spatial and temporal dispersal to examine the prediction that traits of these two dispersal strategies are negatively correlated. Our results suggest that negative covariation is widely anticipated from theory. Empirical studies often reported evidence of weak negative covariation, although more complicated patterns were also evident, including across levels of biological organisation. Existing literature has largely focused on plants with dormancy capability, one or two phases of the dispersal process (emigration and/or transfer) and a single level of biological organisation (theory: individual; empirical: species). We highlight patterns of covariation across levels of organisation and conclude with a discussion of the consequences of dispersal through space and time and future research areas that should improve our understanding of dispersal‐related life‐history syndromes.